The Myth of community : gender issues in participatory developmen t - Guijt, Irene; Shah, Meera Kaul. (New Delhi : Vistaar Publications, 1999)
Papers presented at a two-day workshop at Institute of Development S tudies at University of Sussex, U.K. in December 1993.
Previously published : London : Intermediate Technology Publications , c1998.
Includes bibliographical references and index.
Keywords: Women in development; Women -- Developing countries -- Social conditions; Women -- Developing countries -- Economic conditions